PERSEPSI PESERTA AEROBIK DARI KOMPETENSI INSTRUKTUR AEROBIK UNIVERSITAS NEGERI SEMARANG DI KECAMATAN GUNUNGPATI TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the extent of Aerobics participants' perceptions of the competence State University of Semarang aerobics instructor State University of Semarang in the District of Gunungpati in 2013. The approach used in this study uses a qualitative research approach . The population in this study is the people who follow the State University of Semarang instructor -led aerobics in places as Gunungpati districts . Data collection methods used in this study is a questionnaire survey method , observation and documentation . Methods of data analysis using descriptive percent . The interview results are used to support the research . The results of the data analysis of the study, participants' perceptions of the State University of Semarang competence aerobics instructor in the District of Gunungpati in 2013 showed that the perception of competence Unnes aerobics instructor in the category very well . Perceptions of personal competence gained 92 % in the category of very good , academic competence gained 82 % in the category of very good , professional competence gained 88 % in the criteria very well and social competence gained 92 % in the criteria very well . It can be concluded that the competence Unnes aerobics instructor is very good .